Communicating Science A Global Perspective - Broks, Peter; Gascoigne, Toss; Leach, Joan; Lewenstein, Bruce V.; Massarani, Luisa; Riedlinger, Michelle; Schiele, Bernard (ANU Press, 2020)
Modern science communication has emerged in the twentieth century as a field of study, a body of practice and a profession-and it is a practice with deep historical roots. We have seen the birth of interactive science centres, the first university actions in teaching and conducting research, and a sharp growth in employment of science communicators. This collection charts the emergence of modern science communication across the world. This is the first volume to map investment around the globe in science centres, university courses and research, publications and conferences as well as tell the national stories of science communication. How did it all begin? How has development varied from one country to another? What motivated governments, institutions and people to see science communication as an answer to questions of the social place of science? Communicating Science describes the pathways followed by 39 different countries. All continents and many cultures are represented. For some countries, this is the first time that their science communication story has been told.